ANALISIS DIGITAL MARKETING PADA PT TELKOM WITEL YOGYAKARTA - Carolina Amalia Willem; Sujoko Sujoko (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Abstrak. This research aims to evaluate the digital marketing strategy for the Indibiz product owned by PT Telkom Witel Yogyakarta. Data was collected through questionnaires from service users throughout the year 2024 and was analyzed descriptively and tested for validity and reliability using SPSS version 25.0. The results show that the implementation of digital marketing post-digitalization still faces challenges, particularly in the customer journey aspect. The indicators of accessibility and interactivity have the lowest average (3.76). Technical obstacles were also found such as slow loading, failed service access, and less solution-oriented customer service. These findings indicate the need for improvements to enhance the customer experience. Keywords: Customer Experience, Digital Marketing, Indibiz.. Abstrak. Penelitian ini bertujuan menganalisis digital marketing pada produk Indibiz milik PT Telkom Witel Yogyakarta. Metode yang digunakan dalam penelitian ini adalah kuantitatif deskriptif. Data yang digunakan data primer yang diperoleh melalui kuesioner dengan sampel 96 pelanggan Indibiz. Hasil perhitungan arithmetic mean pada indikator Accessibility 3.79, Informativeness 2.57, Interactivity 2.53, Credibility 2.56, dan Irritation 2.58. Hasil penelitian ini menunjukkan penerapan digital marketing pasca-digitalisasi masih menghadapi kendala pada customer experience, hambatan teknis seperti loading lambat, akses layanan yang gagal, serta layanan customer service yang kurang solutif. Temuan ini menunjukkan perlunya perbaikan untuk meningkatkan pengalaman pelanggan. Kata Kunci: Customer Experience, Digital Marketing, Indibiz.